Démolir, transformer ou conserver ? - Olivia Puel (Perspectives Médiévales)
Today, churches are, at all levels of the territory, an inescapable testimony of the Middle Ages. This paper invites to consider the real consequences of the French Revolution on this religious built heritage. Ransacking and destruction are often associated with this troubled period that aimed to establish a new society. However, they were neither systematic nor caused by an anti-religious sentiment but, more often, by an anti-feudal movement. This article considers the case of places of worship located in a small territorial entity: the abbey and parish of Savigny, in the Rhone. Based on abundant modern archives, it attempts to determine how the population and the municipality felt about these three churches - abbey, monastery and parish - which did not suffer the same fate in the second half of the 18th century. Demolish, transform or conserve: the varied, sometimes contradictory, reactions of the different protagonists can be explained by the relations they had had with these buildings since the Middle Ages. The history of monuments is inseparable from the history of mentalities.